2013
DOI: 10.1186/2052-1847-5-18
|View full text |Cite
|
Sign up to set email alerts
|

Is leg compression beneficial for alpine skiers?

Abstract: BackgroundThis study examined the effects of different levels of compression (0, 20 and 40 mmHg) produced by leg garments on selected psycho-physiological measures of performance while exposed to passive vibration (60 Hz, amplitude 4-6 mm) and performing 3-min of alpine skiing tuck position.MethodsPrior to, during and following the experiment the electromygraphic (EMG) activity of different muscles, cardio-respiratory data, changes in total hemoglobin, tissue oxygenation and oscillatory movement of m. vastus l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 51 publications
(61 reference statements)
0
39
0
Order By: Relevance
“…Eight studies were rated at a high risk of reporting bias because they failed to report the key outcomes or provided incomplete information on dependent variables [1,7,20,28,34,59,65,66]. The reasons for this were due to incomplete outcomes reported [7,28,65], and failure to include results for key outcomes [1,20,34,59,65].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies were rated at a high risk of reporting bias because they failed to report the key outcomes or provided incomplete information on dependent variables [1,7,20,28,34,59,65,66]. The reasons for this were due to incomplete outcomes reported [7,28,65], and failure to include results for key outcomes [1,20,34,59,65].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies examined the effects of compression garments on postural regulation in athletes [28,66]. Sperlich et al [66] concluded that no significant improvement in postural regulation with the compression garments in the eyes-closed condition, whereas, Michael et al [28] found otherwise.…”
Section: Resultsmentioning
confidence: 99%
“…Sperlich et al (19) investigated the effects of kneehigh socks that applied compression pressures of 0, 10, 20, 20 and 40 mmHg and observed no effect at any pressure on cardio-respiratory and metabolic parameters during submaximal running. In contrast to this, another study indicated that compression garments exerting pressures of 20 and 40 mmHg may improve alpine skiing performance by enabling a deeper tuck position with attenuated perceived exertion; however the authors indicated that the garment exerting 40 mmHg may reduce blood flow (20).…”
Section: Introductionmentioning
confidence: 85%
“…These studies have mainly investigated immediate (perhaps temporary) effects of wearing compression garments in elite athletic samples. For example, such research has investigated elite alpine skiers [32], female athletes [21], and young athletes with lower limb injuries [2,10,23,38]. Investigations on the impact of wearing compression garments, such as socks, on proprioception to regulate motor performance have been infrequent, with non-athletic samples.…”
Section: Introductionmentioning
confidence: 99%
“…In sports, the standing limb in the kicking action in soccer and taekwondo is important to ensure stability needed for successful execution [25,35]. From an injury prevention perspective, balance deficit that occurs immediately after anaerobic stress and fatigue could affect sports performance and might increase the probability of injuries [29,32].…”
Section: Introductionmentioning
confidence: 99%